Perioperative and Peripartum Management of Patients with Neuromuscular Disease - Williamson, Julie; Edd, Tom; Perez, Geovanny; Provost, Karin (Seminars in Respiratory and Critical Care Medicine, 2025)
Patients with neuromuscular disease are living longer with advancements in respiratory assistive devices for airway clearance and ventilatory support. This technology has been successfully applied to the perioperative and peripartum periods, making these previously prohibitively high-risk procedures now a risk-controlled intervention. This review will cover preoperative planning and assessment, key intraoperative management interventions, postoperative management, and peripartum management for patients with neuromuscular disorders.
Keywords: perioperative; postoperative; neuromuscular disease; pregnancy